How do you solve the exponential equation 81^(3-x)=(1/3)^(5x-6)? Precalculus Algebraic Modeling Solving Problems Algebraically and Graphically 1 Answer 冠廷 李. May 2, 2017 x=-6 Explanation: 81^(3-x)=(1/3)^(5x-6) (3^4)^(3-x)=(3^-1)^(5x-6) 3^(12-4x)=3^(-5x+6) 12-4x=-5x+6 x=-6 Answer link Related questions What does it mean to solve a problem algebraically? What is a sample problem to solve algebraically? What does it mean to solve a problem graphically? What is a sample problem to solve graphically? How do I find f(3) from the graph of f(x) = x^2 - 4x + 3? How do I find f(x) if its graph includes {(1, 5), (2, 8), (3, 11)}? How can I use a graph to write an algebraic function? How do I use algebra to find a graph's x-intercept? Given vectors u=<4,1> & v=<1,3>, how would I determine the quantity 3u*-2v? How do you solve x^3 + 4x^2 - 20x = 80? See all questions in Solving Problems Algebraically and Graphically Impact of this question 4967 views around the world You can reuse this answer Creative Commons License